2018
DOI: 10.1007/s10535-018-0773-8
|View full text |Cite
|
Sign up to set email alerts
|

Aerenchyma development in different root zones of maize genotypes under water limitation and different phosphorus nutrition

Abstract: Root cortical aerenchyma (RCA) is suggested to reduce metabolic cost for root growth, but it might lower water uptake by plants. The objective of this work was to evaluate the effects of drought and phosphorus on the RCA development along the root axis and to elucidate its role in water stress tolerance of two maize genotypes. Plants of drought-tolerant DKB390 and drought-sensitive BRS1010 genotypes were grown in Vermiculite at field capacity of 100, 75, 50, and 25 % and supplied with 0.1, 0.4, and 0.8 mM phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In addition to those mentioned above, there are many types of evidence indicating the effect of suboptimal P availability on aerenchyma formation in a well-aerated nutrient solution (Gahoonia et al, 2001;Díaz et al, 2018;Schneider and Lynch, 2018;Sou et al, 2019). There was a higher percentage of aerenchyma formation in the cortex of middle and basal sections of roots of both Pi-efficient and Pi-inefficient genotypes grown under P deficiency conditions.…”
Section: Discussionmentioning
confidence: 96%
“…In addition to those mentioned above, there are many types of evidence indicating the effect of suboptimal P availability on aerenchyma formation in a well-aerated nutrient solution (Gahoonia et al, 2001;Díaz et al, 2018;Schneider and Lynch, 2018;Sou et al, 2019). There was a higher percentage of aerenchyma formation in the cortex of middle and basal sections of roots of both Pi-efficient and Pi-inefficient genotypes grown under P deficiency conditions.…”
Section: Discussionmentioning
confidence: 96%
“…The increase amplitude induced by drought was significantly higher when P availability was 5 μM compared to 10 μM ( Figure 6 ). Many studies have shown that drought can amplify the effect of P deficiency by reducing the uptake of P, lowering the P concentration in cytoplasm, and reducing the ATP level in the chloroplast matrix ( Tezara et al., 1999 ; Radersma et al., 2005 ; Diaz et al., 2018 ; Pereira et al., 2023 ). In contrast, P application can alleviate the stress effect of drought by enhancing photosynthesis through increasing the content of chlorophyll, intercellular CO 2 concentration, and leaf area ( Tariq et al., 2017 ; Wu et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, substantially elevated RCA and CCS have been observed in barley, wheat and rice exposed to water stress, which was shown to be the result of the development of an elevated number of xylem vessels [ 26 , 27 ]. Water stress also negatively affects the RCA in the root hairs of maize, but it improves the RCA of mature roots [ 28 ]. Zhu et al [ 29 ] demonstrated that the formation of RCA enhances the drought tolerance of maize, mainly because the adapted root architecture provides more airspace, which reduces the level of root respiration.…”
Section: Introductionmentioning
confidence: 99%